Pengembangan Booklet Terintegrasi Nilai Preventif Gangguan Sistem Sirkulasi Manusia untuk Peserta Didik SMA: (Development of Booklet an Integrated of Preventing Value on Human Circulatory System Disease for Senior High School Students) - Ririn Syafrina; Relsas Yogica Relsas Yogica; Elsa Yuniarti Elsa Yuniarti; Rahmawati Darusyamsu Rahmawati Darusyamsu (BIODIK, 2023)
Adolescent knowledge in maintaining physical health can be increased through teaching materials that are integrated with preventive values ​​in schools. The purpose of this study is to produce an integrated booklet of the value of preventing disiase of the human circulatory system that is valid and practical. The type of research is research and development using the ADDIE development model. The data analysis technique used is descriptive quantitative. The booklet assessment was carried out by a validator consisting of two biology lecturers, FMIPA UNP and one biology teacher, and a practical test was conducted on one biology teacher and 30 students of SMAN 1 Bonjol. Based on the results of the validity test, the percentage of booklet assessment is 91.23% with a very valid category, while the results of the practicality of the booklet assessment percentage is 91.53% with very practical criteria. It can be concluded that the integrated booklet of the preventive value of human circulatory system disiase for high school students has met the criteria and can be used by students in the biology learning process. Key words: Booklet, Preventive Value, Circulatory System Disiase ABSTRAK Pengetahuan remaja dalam menjaga kesehatan tubuh dapat ditingkatkan melalui bahan ajar yang diintegrasikan nilai preventif di sekolah. Tujuan penelitian ini menghasilkan booklet terintegrasi nilai preventif gangguan sistem sirkulasi manusia yang valid dan praktis. Jenis penelitian yaitu penelitian dan pengembangan menggunakana model pengembangan ADDIE. Teknik analisis data yang digunakan adalah deskriptif kuantitatif. Penilaian booklet dilakukan oleh validator yang terdiri dari dua orang dosen biologi FMIPA UNP dan satu orang guru biologi dan dilakukan uji praktikalitas kepada satu orang guru biologi dan 30 peserta didik SMAN 1 Bonjol. Berdasarkan hasil uji validitas presentase penilaian booklet sebesar 91,23% dengan kategori sangat valid sedangkan hasil praktikalitas presentase penilaian booklet sebesar 91,53% dengan kriteria sangat praktis. Dapat disimpulkan bahwa booklet terintegrasi nilai preventif gangguan sistem sirkulasi manusia untuk peserta didik SMA sudah memenuhi kriteria dan dapat digunakan oleh peserta didik dalam proses pembelajaran biologi. Kata kunci: Booklet, Nilai Preventif, Gangguan Sistem Sirkulasi